Evaluation of Rainwater Quality for its Utilization and Domestic Use in the City of Ibagué, Tolima, Colombia - Ramírez Arcila, Hildebrando; Ospina Zúñiga, Oscar E. (Ingeniería Solidaria, 2014)
The article presents the results of the research project “Evaluation of Rainwater Quality for its Utilization and Domestic Use in the City of Ibague” (“Evaluación de la calidad del agua lluvia para su aprovechamiento y uso doméstico en la ciudad de Ibagué”) carried out at the Ibague campus of the Universidad Cooperativa de Colombia in 2012. The research problem arose from interest in studying the potential for utilization of rainwater as an alternative source for domestic use based on determining its physical-chemical and microbiological conditions. The research involved eight sampling stations from which water was taken without any surface contact. The description included measuring turbidity, apparent color, ph, conductivity, temperature, nitrates, total alkalinity, chlorides, aluminum, total strength, total iron, and total sulfates and coliforms. The analysis showed that its physical-chemical composition is susceptible to purification given the lack of harmful levels of contamination. On the contrary, most of the parameters analyzed are within the required ranges for possible water purification, with the exception of ph and turbidity at certain sampling points. It would thus be possible to determine the potential utilization of rainwater after a conventional treatment process to remove certain contaminants that were detected, such as total coliforms, reduction of turbidity, and neutralization of the ph because its low values indicate slightly acidic water.
Keywords: water quality; rainwater; domestic use; analysis; Ibagué